Groups having unique faithful irreducible Q-representation - Vikas Jadhav (Ratio Mathematica)
In this paper, we give few sufficient conditions for finite p-group to have unique NEW (i.e faithful irreducible) Q-representation. As a consequence of these conditions we will prove that any finite p-group of nilpotency class 2 has atmost one NEW Q-representation. We also give examples of few classes of finite p-groups which has unique NEW Q-representation.